Research progress of micro-nano-bubbles in environmental remediation field - Chen, Qin; Zhu, Xinjie; Guo, Yaoguang; Zhou, Quanfa (Frontiers in Environmental Science, 2025)
IntroductionMNBs (MNBs), relying on its special chemical and physical properties, such as high surface potential, long stability and free radical generation capacity, have shown broad application prospects in environmental remediation.MethodsBased on 508 related papers in the Web of Science database, this paper conducts a scientific knowledge mapping analysis using VOSviewer and CiteSpace software to reveal the research situation and trends. Researches show that MNB technology demonstrates remarkable effects in water pollution control (industrial wastewater, surface water, and groundwater) and soil pollution remediation.Results and DiscussionFor instance, ozone MNBs can increase the removal rate of plastic pollutants in industrial wastewater to 94.18% and enhance the degradation efficiency of polycyclic aromatic hydrocarbons through interfacial reactions. In soil remediation, their synergistic effect with surfactants can improve the petroleum pollutants’ removal efficiency. From the perspective of research hotspots, the coupling of MNBs with advanced oxidation technologies (such as Fenton, plasma, and photocatalysis) has become the mainstream direction, significantly enhancing the degradation efficiency of pollutants through interfacial effects and radical generation mechanisms. The author collaboration network indicates that Chinese scholars have made outstanding contributions. The team led by Hu Liming from Tsinghua University has achieved fruitful results in groundwater remediation using ozone MNBs. However, the international cooperation network still needs to be strengthened. In terms of institutional collaboration, the Chinese Academy of Sciences (CAS) leads in both the volume of publications and academic influence, with its research covering multiple application areas such as semiconductor cleaning and membrane treatment. Keyword co-occurrence analysis divides the research topics into three major categories: degradation mechanisms, ozone MNB technology, and multi-technology coupling applications. Among them, “free radicals”, “mass transfer”, and “photocatalysis” are the core keywords. Although MNB technology has achieved phased progress, its long-term stability in complex environments, large‐scale application costs, and cross-disciplinary collaborative mechanisms still need in-depth exploration.